Ursolic acid induces colorectal cancer cells ferroptosis via regulation of system xc- and miR-214-3p/Stat3/GPX4 axis - Shi, Yao; Ma, Changju; Tang, Xiaojuan; Su, Haojie; Lu, Yue; Wei, Jianan; Li, Li; Huang, Tianhua; Wang, Xicheng; Qin, Xintian; Ding, Ying; Han, Ling; et al. (Frontiers in Immunology, 2025)
Background and aimColorectal cancer (CRC) is a prominent worldwide health concern because of its high prevalence and mortality rates. This study explored the role of Ursolic Acid (UA) in preventing the development of CRC and clarified potential mechanisms.Experimental procedureDifferential genes between human normal tissues and colon adenocarcinoma tumor tissues, plus survival analysis were generated on GEPIA2 website. RNA-seq was utilized to screen therapeutic targets after UA added into HT29 cells. AutoDock Vina 1.2.3 was used to carry out molecular docking between GPX4 and UA. Dual-luciferase reporter method was applied to evaluate miR-214-3p/GPX4 and miR-214-3p/Stat3 sponging. Gene overexpression plasmids, miRNA mimics and inhibitors transfection assays were carried out. The morphological alterations in mitochondria were detected based on transmission electron microscopy (TEM). In vivo, the xenograft model of HT29 cells transfected with luciferase gene (HT29-luc) was constructed in nude mice.Key resultsWe found that UA substantially inhibited the proliferation of CRC cells, induced cellular ferroptosis by decreasing the expression of system xc- (SLC7A11 and SLC3A2) and GPX4. Overexpression of Stat3 increased GPX4 expression level. MiR-214-3p mimics can reduce GPX4, p-Stat3 and Stat3 expression levels. MiR-214-3p can bind both GPX4 and Stat3 mRNA 3’UTR. Overexpression of GPX4 and miR-214-3p inhibitors accelerated CRC cells proliferation. MiR-214-3p inhibitors can reverse UA-reduced GPX4 and Stat3 mRNA expression levels. TEM images showed that mitochondrial volume decreased, bilayer membrane density increased, mitochondrial cristae decreased after intervention with UA or miR-214-3p mimics. According to in vivo experiments, UA inhibited CRC tumor growth by regulation of above genes.Conclusions and implicationsThis study demonstrated that UA could effectively inhibit CRC proliferation by inducing ferroptosis via regulation of system xc- subunits and miR-214-3p/Stat3/GPX4 axis, suggesting UA could serve as a promising anti-colorectal cancer candidate requiring further validation and optimization.